Neurofeedback for anxiety symptoms among University students - Jasmine Adela Mutang; Chua, Bee Seok; Shazia Iqbal Hashmi (Science Publishing Corporation Inc., 2018)
Anxiety is a common, universal human emotion, but excessive feelings of anxiety can negatively affect one’s life satisfaction and quality of life. Psychotherapy and medication are the most common forms of intervention for anxiety disorders. In a recent development, researchers suggested that neurofeedback training (NFT) has the potential to reduce symptoms of anxiety, claiming to be less invasive while carrying fewer side effects compared to medication. Therefore, this preliminary study sought to assess whether neurofeedback training is a viable method to improve symptoms of anxiety in the nonclinical sample. Participants were randomly assigned to two groups (neurofeedback training group or a control group). Anxiety symptoms were assessed using the Depression, Anxiety and Stress Scale (DASS-21), the Beck Anxiety Inventory (BAI), and the State-Trait Anxiety Inventory (STAI). The findings showed an overall improvement in all of the psychological measurements in the neurofeedback group hence provide additional evidence to the field of neurotherapy that neurofeedback training is a viable option to improve anxiety symptoms among university students.